Antimicrobial sensitivity of faecal Escherichia coli isolated from backyard broiler chickens in Chitungwiza, Zimbabwe - Jonker, Annelize (University of Pretoria, 2024)
Mini Dissertation (MSc (Tropical Animal Health))--University of Pretoria 2024.